Consumer in the Buy Now, Pay Later Market – Opportunities and Threats - Ziemba, Marika (Journal of Finance and Financial Law, 2024)
The purpose of the article. The purpose of the article is to identify opportunities and threats for consumers related to BNPL payments.Methodology. The article uses the analysis of existing data (in particular the current reports on the BNPL sector) and the results of a questionnaire survey. The CAWI questionnaire survey was conducted on a group of 100 people (50 women and 50 men) in January–February 2024. The survey was addressed to the group of people aged 25–34 due to the fact that, in the light of literature research, people of this age most often use deferred payments. The survey was sent to graduates of the Faculty of Economics and Sociology of the University of Lodz who fit into the deferred payment customer profile.Results of the research. The article identified opportunities and threats for customers of the BNPL sector, highlighted a profile of a customer using deferred payments, and presented the legal and psychological aspects related to deferred payments. Additionally, the article compared BNPL payments with credit cards, bank loans and non-bank loans, and related the results to the potential risk of over-indebtedness.